2019
DOI: 10.1055/a-0799-9630
|View full text |Cite
|
Sign up to set email alerts
|

Akute makuläre Neuroretinopathie

Abstract: Zusammenfassung Hintergrund Die akute makuläre Neuroretinopathie (AMNR) ist eine seltene, ein- oder beidseitige Erkrankung der Makula. Betroffene Patienten, zumeist junge Frauen, beklagen plötzlich aufgetretene Zentralskotome. Diese korrespondieren mit scharf begrenzten rötlich-braunen makulären Läsionen. Ophthalmoskopisch sind sie häufig kaum auszumachen, eine deutlich bessere Darstellung erlaubt das Infrarotreflexionsbild. Es zeigt sich eine oft blütenartige Gruppierung der flachen ovalen oder keil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
3
Order By: Relevance
“…With regard to the clinical examination, fundoscopy can show flat, wedge-shaped or teardrop-shaped lesions with a reddishbrown or orange coloration in the macular region [16]. Due to the oftentimes very subtle formation of visible retinal changes, the fundoscopy can also be normal.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With regard to the clinical examination, fundoscopy can show flat, wedge-shaped or teardrop-shaped lesions with a reddishbrown or orange coloration in the macular region [16]. Due to the oftentimes very subtle formation of visible retinal changes, the fundoscopy can also be normal.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Im Hinblick auf die klinische Untersuchung können sich funduskopisch flache, keil- oder tropfenförmige Läsionen in rötlich-brauner oder orangefarbener Färbung im Makulabereich zeigen 16 . Durch die oftmals sehr dezente Ausprägung sichtbarer retinaler Veränderungen kann sich die Funduskopie auch unauffällig darstellen.…”
Section: Zusammenfassung Und Diskussionunclassified
See 2 more Smart Citations
“…However, this patient was older and had CRVO in his right eye, with a history of hypertension, which was different from previous reported cases. In 2019, Wyss et al [ 7 ] reported four cases, all young women, involving AMN with focal abnormalities in the photoreceptor outer segments. In the same year, Imran Ashfaq et al [ 8 ] also reported four cases of AMN aged 18–32 years associated with confirmed influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%